2003
DOI: 10.1007/s11738-003-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous phenolic contents, peroxidase and polyphenoloxidase activities in date palm (Phoenix dactylifera L.) offshoots related to rooting ability

Abstract: Offshoots from three cultivars of date pahn showed different rooting ability, in response to the same root inducing treatment (25 mM indole butyric acid), under misting system. Offshoots from Mejhoul rooted easily and produced numerous roots, while those from Khalt rooted poorly and produced fewer roots. No relationship was found between soluble and ionically bound peroxidase and polyphenoloxidase activities and phenolics level, determined spectrophotometrically in the offshoot leaves prior to the auxin applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…As described above, such a relationship was found in olive by Macedo et al (2013) while studying the evolution of POX and PPO activities during IBA-induced adventitious root formation of microcuttings of the difficult-to-root 'Galega vulgar'. The inverse trend of POX and PPO activities had been previously described by Qaddoury and Amssa (2003) and by Cheniany et al (2010) who attributed the decrease in PPO activity to an accumulation of monophenolic compounds, which in turn stimulated POX activity. The results found in olive are in agreement with those described for grapevine (Vitis vinifera, Kose et al, (2011); Yilmaz et al, (2003), Camellia sinensis Rout (2006)) and walnut (Juglans regia, Cheniany et al, (2010).…”
Section: Role Of Oxidative Enzymesactivity and Isoformssupporting
confidence: 64%
See 1 more Smart Citation
“…As described above, such a relationship was found in olive by Macedo et al (2013) while studying the evolution of POX and PPO activities during IBA-induced adventitious root formation of microcuttings of the difficult-to-root 'Galega vulgar'. The inverse trend of POX and PPO activities had been previously described by Qaddoury and Amssa (2003) and by Cheniany et al (2010) who attributed the decrease in PPO activity to an accumulation of monophenolic compounds, which in turn stimulated POX activity. The results found in olive are in agreement with those described for grapevine (Vitis vinifera, Kose et al, (2011); Yilmaz et al, (2003), Camellia sinensis Rout (2006)) and walnut (Juglans regia, Cheniany et al, (2010).…”
Section: Role Of Oxidative Enzymesactivity and Isoformssupporting
confidence: 64%
“…However, the results are not clear, the putative protein was not further purified and the conclusions drawn are merely speculative. On the contrary, in narrow-leafed ash (Fraxinus angustifolia, (Tonon et al, 2001) another species of the Oleaceae family, POX activity increased in the expression phase, as described also in other species like date palm (Phoenix dactylifera, (Qaddoury and Amssa, 2003), Camellia sinensis (Rout, 2006) and apple (rootstock MM106, (Naija et al, 2009)). This is supported by findings of Tartoura et al (2004) who suggested that POX (IAAox) is only involved in initiation and expression of adventitious roots, as during root induction IAA conjugation is the most likely cause of downregulation of IAA levels.…”
Section: Role Of Oxidative Enzymesactivity and Isoformsmentioning
confidence: 65%
“…Such mediators seem to function in the signalization route during adventitious root formation (QADDOURY; AMSSA, 2003;LI et al, 2009;XUE, 2010;LIMA et al, 2011a).…”
Section: +mentioning
confidence: 99%
“…For these reasons, it has been suggested that the level of POX activity can be evaluated as an indicator of the successive phases in adventitious rooting 22, 23. In addition to POX activity, polyphenol oxidase (PPO) is another enzyme which is thought to be involved in the initiation and development of adventitious roots 24–26…”
Section: Introductionmentioning
confidence: 99%
“…Adventitious root formation of grapevine ( Vitis vinifera ) genotypes can change according to its genotypes and the cuttings of some genotypes easily form adventitious roots, whereas other genotypes are very recalcitrant or intermediate 9–27. Therefore, the breeding program for grapevine, particularly its recalcitrant genotypes, is very time consuming because these genotypes have long generation times and slow/low rooting 27.…”
Section: Introductionmentioning
confidence: 99%